2017
DOI: 10.21037/jtd.2017.03.82
|View full text |Cite
|
Sign up to set email alerts
|

Molecular strategies in the management of bronchopulmonary and thymic neuroendocrine neoplasms

Abstract: Thoracic NETs [bronchopulmonary NETs (BPNETs) and thymic NETs (TNET)] share a common anatomic primary location, likely a common cell of origin, the "Kulchitsky cell" and presumably, a common etiopathogenesis. Although they are similarly grouped into well-differentiated [typical carcinoids (TC) and atypical carcinoids (AC)] and poorly differentiated neoplasms and both express somatostatin receptors, they exhibit a wide variation in clinical behavior. TNETs are more aggressive, are frequently metastatic, and hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 81 publications
1
10
0
1
Order By: Relevance
“…Recent studies have suggested that mRNA transcript analysis in blood can identify thymic neuroendocrine tumors Table 1 Modified proposal for a "morphomolecular grading system" of thymic neuroendocrine tumors ( Modified from Dinter et al [19]) NEC neuroendocrine carcinoma a Proposed morphomolecular thymic neuroendocrine tumor grade b Carcinoid morphology subtypes also include typical and atypical carcinoids as well as NET G3; the latter is similar to grade-discordant gastroenteropancreatic tract neuroendocrine tumors that are characterized by a well-differentiated (carcinoid) morphology and mitotic count like G2 tumors but increased Ki-67 index (> 20%) equivalent to G3 tumors [107] c Pos, expressed [5]. Three non-secretory atypical carcinoid tumors (i.e., no production of serotonin or ACTH) with low chromogranin A levels were found to have detectable expression of genes that have been linked to neuroendocrine tumor pathobiology in the circulating blood using the NETest [5,67]. However, these findings need to be validated in larger cohorts and their clinical utility in identifying progressive tumors, confirming complete tumor resection, and predicting treatment response has to be established.…”
Section: Molecular Background Of Thymic Neuroendocrine Tumors (Carcinmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have suggested that mRNA transcript analysis in blood can identify thymic neuroendocrine tumors Table 1 Modified proposal for a "morphomolecular grading system" of thymic neuroendocrine tumors ( Modified from Dinter et al [19]) NEC neuroendocrine carcinoma a Proposed morphomolecular thymic neuroendocrine tumor grade b Carcinoid morphology subtypes also include typical and atypical carcinoids as well as NET G3; the latter is similar to grade-discordant gastroenteropancreatic tract neuroendocrine tumors that are characterized by a well-differentiated (carcinoid) morphology and mitotic count like G2 tumors but increased Ki-67 index (> 20%) equivalent to G3 tumors [107] c Pos, expressed [5]. Three non-secretory atypical carcinoid tumors (i.e., no production of serotonin or ACTH) with low chromogranin A levels were found to have detectable expression of genes that have been linked to neuroendocrine tumor pathobiology in the circulating blood using the NETest [5,67]. However, these findings need to be validated in larger cohorts and their clinical utility in identifying progressive tumors, confirming complete tumor resection, and predicting treatment response has to be established.…”
Section: Molecular Background Of Thymic Neuroendocrine Tumors (Carcinmentioning
confidence: 99%
“…Thymic neuroendocrine tumors represent less than 5% of all thymic and mediastinal neoplasms and 0.4% of all neuroendocrine tumors. In general, thymic neuroendocrine tumors behave more aggressively than pulmonary neuroendocrine tumors, they are frequently metastatic, and 5-year survival is not reached in approximately 50% [ 5 ]. Patients with these tumors are typically symptomatic, often secrete ectopic hormones (e.g., ACTH in 40% of tumors) and, like neuroendocrine tumors of the lung, secrete circulating biomarkers such as chromogranin A and 5-HIAA (metabolite of serotonin).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IHC staining helped to determine the primary tumor site. According to the literature, TTF‐1 is positive in IHC staining in 12% of patients with thymic NEN, PAX‐8 in 50%, and NKX6‐1 in 0% 5–7 . TTF‐1 is positive in 7% of patients with pancreatic NEN, PAX‐8 in 32%, and NKX6‐1 in 82% 6 .…”
Section: Discussionmentioning
confidence: 98%
“…The blood transcriptome-based marker NETest has been validated as a diagnostic and prognostic biomarker for neuroendocrine neoplasms in various scenarios. [28][29][30][31] However, in the context of VHL-related PNETs, there are not sufficient data to suggest its use at this time point.…”
Section: Detailed Recommendations For Vhl-related Pancreatic Manifestationsmentioning
confidence: 99%